Brain Structural Connectivity Predicts Brain Functional Complexity: Diffusion Tensor Imaging Derived Centrality Accounts for Variance in Fractal Properties of Functional Magnetic Resonance Imaging Signal. (1st July 2020) - Neudorf, Josh; Ekstrand, Chelsea; Kress, Shaylyn; Borowsky, Ron
Highlights: Fractal analysis of fMRI BOLD and graph theory of DTI were examined. fMRI BOLD complexity (measured by Hurst exponent) related to measures of centrality. Eigenvector, degree, and PageRank centrality were consistently and positively related to complexity. Thalamus and hippocampus notably showed high centrality and complexity. Abstract: The complexity of brain activity has recently been investigated using the Hurst exponent (H), which describes the extent to which functional magnetic resonance imaging (fMRI) blood oxygen-level dependent (BOLD) activity is simple vs. complex. For example, research has demonstrated that fMRI activity is more complex before than after consumption of alcohol and during task than resting state. The measurement of H in fMRI is a novel method that requires the investigation of additional factors contributing to complexity. Graph theory metrics of centrality can assess how centrally important to the brain network each region is, based on diffusion tensor imaging (DTI) counts of probabilistic white matter (WM) tracts. DTI derived centrality was hypothesized to account for the complexity of functional activity, based on the supposition that more sources of information to integrate should result in more complex activity. FMRI BOLD complexity as measured by H was associated with five brain region centrality measures: degree, eigenvector, PageRank, current flow betweenness, and current flow closeness centrality. Multiple regression analyses demonstrated that eigenvector centrality was the most robust predictor of complexity, whereby greater centrality was associated with increased complexity (lower H ). Regions known to be highly connected, including the thalamus and hippocampus, notably were among the highest in centrality and complexity. This research has led to a greater understanding of how brain region characteristics such as DTI centrality relate to the novel Hurst exponent approach for assessing brain activity complexity, and implications for future research that employ these measures are discussed.